Comparative Analysis of Morphological Indicators of Street Workout Athletes with Different Training Experience - Olha Podrihalo; Leonid Podrigalo; Sergii Iermakov; Zhanna Sotnikova-Meleshkina; Konstantin Sokol; Olexandr Podavalenko; Olexsandr Halashko; Tetiana Yermakova (OVS LLC, 2021)
Purpose. The purpose of the article is a comparative analysis of the morphological indicators of street workout (StW) athletes with different training experience (TE).  Materials and methods. The study involved StW athletes (n = 27). Athletes were divided into two groups: StW-1 (n = 13, age 15.15 ± 0.44 years, TE 1.56 ± 0.22 years); StW-2 (n = 14, age 16.57 ± 0.48 years, TE 2.64 ± 0.53 years). The body length and body mass were measured; the level and harmony of physical development were evaluated. The regression method was used. The handgrip was evaluated by hand dynamometry indicators Camry EH101 electronic dynamometer (China). The handgrip was measured by the maximum grip frequency in 10 s the electronic device "Kepai" (China). The content of muscle and adipose tissue were determined by the body composition monitor OMRON BF-511 (Japan).  Results. The average value of the strength index in the StW-1 was more than 60%, and in the StW-2 was more than 70%. The StW-2 had a significant excess of the hand dynamometry, power index, impulse index of both hands; index of static and dynamic grip of the left hand; specific weight of muscles. The average level of physical development was observed in (61.54 ± 13.49)%, above the average was observed in (23.08 ± 11.69)% of StW-1. Harmonious physical development had (38.46 ± 13.49)%. In StW-2, the average level of physical development had (64.29 ± 12.81)%, above the average had (21.43 ± 10.97)%. Harmonious physical development had (50.00 ± 13.36)%. In StW-1 (46.15 ± 13.83)% had a normal fat content and a fat level below normal. In StW-2, the normal fat content had (30.77 ± 12.80)%, and the low adipose tissue content was (69.23 ± 12.80)%.  Conclusions. All athletes had a high content of muscle tissue. It was confirmed the specific effect of StW on the body of athletes. Grip strength, specific weight of muscle component are predictors of success. The information content of the proposed indices for monitoring the functional state of athletes was confirmed.